Effect of an Educational Intervention on the Knowledge about Traumatic Brain Injury Guidelines among Clinical Nurses - Subramaniam, Sivakami; Prabhakar, Preetham; Kanagaraj, Umadevi; Baby, Priya (Indian Journal of Neurotrauma, 2021)
Objective Traumatic brain injury (TBI) is a major cause of death and disability throughout the world including developing countries like India. Adherence to guideline based TBI management has proven to decrease death rate and improve neurological outcomes. This study aimed to assess the knowledge of TBI guidelines among clinical nurses caring for TBI patients, and to determine the effect of an educational intervention on their knowledge.Methods Preexperimental, one group pretest and posttest design was used. A purposive sample of 60 nurses was included in the study. A structured questionnaire was prepared to assess the knowledge of nurses. Educational intervention was given in the form of a planned teaching program that was prepared based on the national TBI guidelines.Results There was a significant gain in the knowledge scores of the nurses after the educational intervention when compared with the knowledge scores before the intervention (p = 0.001) Nurses who were experienced more than 10 years were found to have significantly higher knowledge score than others with lesser years of experience.Discussion This study demonstrates important knowledge gap about TBI guidelines among clinical nurses. Educational interventions can be effectively used to improve the knowledge about TBI guidelines among nurses.
Keywords: traumatic brain injury; clinical guidelines; nurses; knowledge; educational intervention